WRITING STYLES SPECIFIC TO MANUSCRIPTS - Gulinur Xamidova, daughter of Alisher; Baisov Ahmad Sobirjonovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  provides  detailed  information  about  writing  and  its evolution. Various types of writing are analyzed during its developmental stages. It proves the significant importance of writing in our daily lives and linguistic studies. Additionally, types of writing are illustrated with examples and their usage scenarios are examined.